THE ROLE OF UNITED NATION MISSION IN CONFLICT RESOLUTION IN SOUTH SUDAN - Dr. Alier,; Bill, Dut Bol Ayuel (IJRDO - Journal of Social Science and Humanities Research, 2022)
The purpose of the study was to investigate the on the Role of United Nation Mission in Conflict Resolution in South Sudan .The study did not cover entire South Sudan but a number of individuals from selected areas were taken to represent the population. The officials of United Nation Mission were included to established non-governmental organization humanitarian role in peace building and their influence in United Nation Mission in South Sudan.The issue on how non-governmental organization use scarce resource management method to address conflict were analyzed. The study established mean through which United Nation Mission provide forums for conflicting community in South Sudan to sort out differences.The study identified the possible ways through which United Nation Mission in South Sudan could facilitate public awareness about peace building in South Sudan. The study established which humanitarian Actors and non-governmental organization play role in peace building and what their influence is among community in South Sudan. The research sought answer on how United Nation Mission provide forum for peace building to communities in South Sudan. The study employed human needs theory developed in 1970 and 1980 as generic or holistic theory of human behavior. It is on hypothesis human have basics needs that have to meet in order to maintain stable societies as John Burton describes.The research design adapted in this study was survey in which the research went to the field to collect data directly. The sample size in this study was 50 respondents here the researcher employed simple random sampling techniques to select 100 respondents from population. Questionnaires and interviews were used to collect data. Data analysis was presented in tables with emphasis to frequencies and percentages. The study established that United Nation Mission play crucial role in peace building in South Sudan.The study found out that Humanitarian Assistance provides food, clothing, water and tents in case of calamity. This was attribute to the facts that basics needs and health services are basic for the survival of every community. Through humanitarian assistance like food, relief, clothing, water and tents which are underlying causes of conflicts